Dosimetric investigation of couch rotation angles in non-coplanar VMAT plans for lung cancer SBRT - Ye, Weiqiang; Wang, Housheng; Wei, Zhenzhen; Zhang, Wei; Yu, Chaojun; Zhang, Dawei; Su, Shida; Qin, Wen; Hu, Kai; Li, Bo (Frontiers in Oncology, 2024)
BackgroundThis study aimed to investigate the effect of couch rotation angles on non-coplanar volumetric modulated arc therapy (ncVMAT) plan for stereotactic body radiotherapy (SBRT) in lung cancer patients and to evaluate the feasibility of clinically applying ncVMAT for SBRT.MethodsTwenty-four lung cancer patients with a single lesion eligible for SBRT were enrolled in the study. Seven dual partial-arc VMAT plans with varying couch angles were designed for every patient. These plans utilized two partial arcs, with the same first arc set at a fixed 0° couch angle in all plans. The second arc’s couch angle varies at 15° intervals, ranging from 0° to 90°. The plans are designated as C0, NC15, NC30, NC45, NC60, NC75, and NC90, respectively. Plan evaluation included assessment of the maximum dose (Dmax), the mean dose (Dmean), homogeneity index (HI), conformity index (CI), and the ratio of the 50% isodose volume to the planning target volume (R50%). Dosimetric parameters for organs at risk such as the ipsilateral lung, contralateral lung, bilateral lungs, esophagus, trachea, chest wall, heart, and spinal cord were analyzed. Additionally, plan complexity-related metrics included modulation degree (MD), delivery time (DT), and monitor unit (MU) were assessed.ResultsAs the couch rotation angle increased, parameters such as Dmax, Dmean, HI, CI, R50%, V20Gy, V25.75Gy and V30Gy of the ipsilateral lung and bilateral lungs, V10Gy of the contralateral lung and Dmean of the chest wall varied, while MD, MU, and DT increased. Compared to C0, the Dmax, Dmean, and HI of the planning target volume (PTV) decreased from 6728.35 ± 209.56cGy, 5743.04 ± 93.45cGy, and 0.281 ± 0.032 to 6500.48 ± 225.26cGy, 5654.81 ± 109.23cGy, and 0.245 ± 0.031, respectively, when the couch was rotated to 90°. The CI increased from 0.859 ± 0.031 to 0.876 ± 0.024. Decreases in R50% were 1.4%, 4.9%, 9%, 13.5%, 16.8%, and 18.4% for NC15, NC30, NC45, NC60, NC75, and NC90, respectively.ConclusionsIn the treatment of lung cancer using SBRT, ncVMAT plans demonstrate superior dose distribution and deliver lower doses to certain OARs compared to cVMAT plans. This advantage becomes more pronounced with increasing couch rotation angles. Our study offers theoretical support for the preferential use of ncVMAT plans in lung cancer SBRT and provides empirical evidence to guide the selection of optimal couch rotation angles.